The Contribution of Pedagogic Competence, Personality, and Work Ethic to the Performance of Physical Education Teachers at Elementary Schools in Kembang District, Jepara Regency (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
The purpose of this research is to analyze the contribution of pedagogic competence, personality competence, and work ethic to the performance of elementary school physical education teachers in Kembang District, Jepara Regency. This type of research uses a non-experimental quantitative approach, where the researcher examines the facts that have occurred (ex post facto). The method used is correlational. The sample in this study were 19 elementary school physical education teachers and used a total sampling technique. The results of the regression analysis showed that the magnitude of the teacher's performance which was influenced by pedagogic competence, personality competence, and work ethic was 95.4%. Based on the results of the analysis and discussion, it can be concluded that there is a positive contribution between pedagogic competence, personality competence, and work ethic on the performance of elementary school physical education teachers in Kembang District, Jepara Regency, by 95.4%. Recommendations in improving teacher performance need to be held a program to improve and develop teacher competence as well as an assessment of the work ethic of elementary school physical education teachers so that teachers can carry out their profession to the fullest with the provision of competence and a good work ethic.